Challenges and Determinants Influencing Adoption of Portfolio Management Models in Real Estate Investment in South-East Nigeria - Ajogwu, H. A.; Egolum, C. C. (International Journal of Real Estate, 2025)
This study investigates the challenges and determinants influencing the adoption of portfolio management models in real estate investments across South-East Nigeria. Despite the rising interest in real estate as a wealth-building strategy in the region, many investors still rely on informal decision-making approaches rather than structured portfolio tools that can optimize returns and minimize risk. Using a descriptive survey design, data were collected from all 544 registered Estate Surveyors and Valuers operating across the five South-Eastern states. A structured questionnaire divided into two sections captured demographic data and core information related to awareness, challenges, and perceived outcomes of portfolio model adoption. The analysis involved both descriptive and inferential statistics, including multiple regression, conducted via SPSS software. Findings revealed that specific challenges such as limited technical expertise, poor access to market data, and high implementation costs significantly affect the application of portfolio models (R² = 0.149, p < 0.05). Additionally, a statistically significant positive relationship was established between the adoption of portfolio models and real estate investment performance (R² = 0.225, p < 0.05), albeit with a modest effect size. The study concludes that despite these barriers, portfolio models contribute to better decision-making and improved investment outcomes when applied. It recommends that policymakers, academic institutions, and professional bodies should collaborate to improve training, develop localized modeling tools, and enhance digital infrastructure to foster greater adoption. These efforts are essential to modernizing real estate investment practices in the region and promoting long-term financial sustainability.
Keywords: Portfolio Management Models; Real Estate Investment; South-East Nigeria; Investment Performance; Risk Analysis; Model Adoption; Infrastructure Challenges; Institutional Support